Pengaruh Kualitas Layanan dan Kepercayaan terhadap Kepuasan Anggota: Studi Pada Kpri Pengadilan Tinggi Semarang - Sinta Rosita Sari; Ali Maskur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The study was conducted to determine the influence of service quality, trust and satisfaction (case study of KPRI Semarang High Court). The research focuses on service quality and trust, aiming to analyze their influence on satisfaction. The population used in this research were members of the KPRI Semarang High Court. The sample used was 58 respondents using the purposive sampling method. The method for collecting data uses quantitative methods or questionnaires. This research uses instrument test analysis models (validity and reliability tests), multiple linear regression analysis, and model tests (t-test and f-test) in SPSS software. The results of this research conclude that service quality has a positive and significant effect on member satisfaction. Trust has a positive and significant effect on member satisfaction. Satisfaction is proven to have a positive and significant impact on the satisfaction of KPRI members at the Semarang High Court. The variable that most influences the satisfaction of KPRI members at the Semarang High Court is service quality.